Granular Borwn Sugar Home Industry as a Carriage to Enhance Family Social Welfare - Gunanto Surjono (Jurnal Penelitian Kesejahteraan Sosial, 2017)
The goal of this research is to reveal the role of granular brown sugar manufacture to enhance family social welfare done by house wives in Kebonrejo Village. The approach model used in this research is case study, data are gathered through interview, observation, and documnentary analysis related to written activities of brown sugar making process. The research finds that the enhancement of family social welfare of house wives of Kebonrejo Village can be reseached from their success to change their local product from raw field material to ready consumed product (granular brown sugar) that multiple their income. The multiple income effects their ability to purchase house hold needs, sort of more eat and drinks, house hold divices, clothing, health service, and school fee for their children. It is recommended that the departement of social affairs and related institutions having commitment on social empowerment to emphasize their approach especially with local communities having resource and human potential prospect to develop.